Enterprise resource planning : the reluctant champion. - Chin, Wenqi. (2008)
ERP integrates organisational business processes and IT, impacting existing business architecture, processes and people. Champions and consultants, the anointed ones implementing the ERP have to pay greater attention to the business’s vision and organisational structure. This study attempts to reconcile the different perspectives of the champion and the consultant.